credit capacity and its impact on the profitability of commercial banks: A study on a sample of commercial banks in the Iraq Stock Exchange Duration (2005-2018) - Ahmed Faris Al Kaabi, Ali; Khayoun Ashour Al-Jubouri, Zahraa (Iraqi Journal for Administrative Sciences, 2024)
The research aims to measure the impact of credit capacity with its indicators (total loans to total deposits, total loans to total assets, capital adequacy ratio, loan loss provision ratio) on profitability indicators. In its study, it relied on a set of published financial reports and statements for a group of banks listed on the Iraq Stock Exchange, which were selected depending on the extent of data provision for the period of study 2005-2018. The study used a set of financial and statistical means to achieve its goals. The study used simple linear regression between the research variables by using the ready-made statistical program SPSSv.25 application and the Excel program. The study reached a set of conclusions, the most important of which is that the statistical results showed the significance of the relationship between the loan-to-deposit ratio and profitability indicators, meaning that a higher percentage increases the profitability of banks, and this leads to the belief that the main reason for increasing profitability is the decrease in the interest costs paid on deposits or that the income from Loan interest covers the cost of interest on deposits. Then the study concluded with a set of recommendations, the most important of which is the need to rely on clear credit policies that are inspired by the general monetary policy of the Central Bank by reviewing and following up on the directives of the Central Bank for determining interest rates and reserves and developing future plans based on their fundamentals on the development of the banking sector and the economy in general.